A call for health systems to monitor the health‐related quality of life of people living with HIV. Issue 2 (23rd November 2022) - Lazarus, Jeffrey V.; Van Hout, Marie Claire; Fuster‐Ruizdeapodaca, Maria J.; Brown, Graham; Guaraldi, Giovanni
Abstract: Introduction: The World Health Organization's (WHO's) new global health strategy on HIV represents a major step toward a broader conceptualization of HIV care. It recognizes the importance of addressing chronic care more fully and–for the first time ever–the health‐related quality of life (HRQoL) of people living with HIV (PLHIV). Methods: A thorough literature review was conducted in order to analyse how the WHO strategy on HIV for 2022‐2030 addresses the monitoring of the HRQoL of PLHIV for the next decade and compared it to that of other countries and health authorities. Results: Unlike for other issues, the strategy does not include quantitative targets for 2030, thus falling short of committing to monitoring global progress in improving the long‐term well‐being of PLHIV. Conclusions: We urge national health systems not to wait for WHO to lead on this issue. Seeking good HRQoL outcomes for PLHIV can confer far‐reaching benefits on health systems. The feasibility of monitoring population‐level HRQoL has been demonstrated through the use of simple tools like patient‐reported outcome measures (PROMs) and patient‐reported experience measures (PREMs). Many countries can already set HRQoL monitoring targets, similar to those presented in this viewpoint, while we work toward an agreed minimum metric for use by all countries.